Pengaruh Akses Internet, Pendidikan, dan Investasi Terhadap Tingkat Penyerapan Tenaga Kerja Formal - Nihayatul Mumtazah; Lucky Rachmawati (Universitas Negeri Surabaya, 2026)
This study analyzes and empirically tests the determinants of Formal Labor Absorption in Java Island, amidst the challenges of the dominance of the informal sector and the acceleration of digital transformation. The purpose of this study is to analyze the influence of Internet Access, Education, and Investment on the Formal Labor Absorption Rate in 6 provinces in Java Island in the period 2015–2023. This study uses a quantitative approach by utilizing secondary data from the Central Bureau of Statistics of the Republic of Indonesia. This study uses panel data regression analysis techniques. The results of the study indicate that simultaneously, Internet Access, Education, and Investment have a significant effect on the Formal Labor Absorption Rate in Java Island. Partially, Internet Access has a positive and insignificant effect, Education has a negative and significant effect, and Investment has a negative and insignificant effect on the Formal Labor Absorption Rate in Java Island.